Shallow-Water Tsunami Deposits: Evidence from Sediment Cores and Wave Propagation of the 1601 CE Lake Lucerne Event - Valentin Nigg; Paola Bacigaluppi; David F Vetsch; Hendrik Vogel; Katrina Kremer; Flavio S Anselmetti (PANGAEA, 2021)
This datasets includes sediment core scan data (MSCL, XRF), sediment subsample measurements (particle size measurements with a Malvern Mastersizer Laser diffraction analyzer (LDA and Carbon, Nitrogen, and Sulfur (CNS) measurements), lake surface samples (CNS and mean particle size of LDA measurements) from the Lucerne Bay, Lake Lucerne, Switzerland and key wave parameters obtained from virtual gauges of numerical wave propagation with BASEMENT. This datasets has been carried out within the SNSF Singergia project" Lake Tsunami: Causes, Controls, and Hazard".